The Method of Religious Performance of the Sabean-Mandaean Hymns for the Baptismal Ritual - Siwan, Ghassan Lami (Journal of Tikrit University for Humanities, 2023)
The Mandaean religion is one of the ancient and important monotheistic religions in Iraq and Iran. It has its own rituals that are characterized by the use of singing and intonation of speech. It began with the emergence of human creation through a group of prophets (peace be upon them). The present study includes the methodological framework, where the researcher dealt with the research problem, and explained the importance of the research, the objectives and the limits of the terminology. Also, it includes the theoretical framework which dealt with the history of the Sabean Mandaeans, and their religious rituals and sources. It discusses the main books and special secondary books for the Sabean Mandaean hymns, and finally the researcher dealt with the sources of their sacred books and previous studies. The last part of the research includes the findings and the recommendations of the study.